Managing Differences Through Religiousness That Has An Impact In A Fragmented Society: Thoughts On The Sociology Of Religion - Najamuddin; Alimin Alwi; Sopian Tamrin; Hasruddin Nur (Cita konsultindo, 2025)
The phenomenon of modern multicultural societies and diversity of identities often leads to social fragmentation. This paper emphasizes the role of religion as a mediator of social integration, a provider of shared values, and a symbolic space that unites society. This research was conducted using a reflective qualitative approach through literature study and theoretical analysis of the sociology of religion. Data collection techniques involved documentation, specifically the review of academic works, journal articles, and key books in the field of religious sociology relevant to the topics of social integration and religiosity. Meanwhile, data analysis techniques employed thematic content analysis, focusing on the interpretation of meaning, values, and the social functions of religious practices within the context of a multicultural society. The results of the analysis show that open and impactful religious practices can be a middle ground in dealing with the complexity of a fragmented society. This article recommends strengthening inclusive religiosity through education, social policies, and interfaith forums in order to build sustainable social cohesion.